If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -43 = 3(x + -1) + -4 Combine like terms: 15 + -43 = -28 -28 = 3(x + -1) + -4 Reorder the terms: -28 = 3(-1 + x) + -4 -28 = (-1 * 3 + x * 3) + -4 -28 = (-3 + 3x) + -4 Reorder the terms: -28 = -3 + -4 + 3x Combine like terms: -3 + -4 = -7 -28 = -7 + 3x Solving -28 = -7 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -28 + -3x = -7 + 3x + -3x Combine like terms: 3x + -3x = 0 -28 + -3x = -7 + 0 -28 + -3x = -7 Add '28' to each side of the equation. -28 + 28 + -3x = -7 + 28 Combine like terms: -28 + 28 = 0 0 + -3x = -7 + 28 -3x = -7 + 28 Combine like terms: -7 + 28 = 21 -3x = 21 Divide each side by '-3'. x = -7 Simplifying x = -7
| 121c^2-36w^2=0 | | W(6)=250*6 | | 19=p+1 | | -6+3x+8=-210 | | 8a-(-3a)= | | 2x^4+3x^3-2x^2+14x+15=0 | | 4x-8=1+7x | | q-4=69 | | -3(5+5x)=-105 | | 3d=78 | | 1/3(6y-9)=2y=13 | | -14=q3 | | 3.14*35=109.9 | | 3d=73 | | rs+4= | | 50=h+-43 | | 10x-(8/3)-4x=6x | | h=-16t^2+55t+5 | | 3x-3(2x+4)=10 | | 3.14*35= | | h/2=1.63 | | 3(10-4)/(15-3*3) | | -12+20(x)=588 | | 96/0.40 | | 5n^2=1+5n | | f-3=2 | | k/4=3 | | 4x^2+12w+9=49 | | 18x^2-66x-252=0 | | u-4=15 | | a*3+4=10 | | y^2+10y+25-x^2=0 |